Pemberdayaan UMKM Salai Ikan Melalui Digitalisasi Pemasaran dan Manajemen Keuangan di Desa Batumarta II, Kecamatan Lubuk Raja, Kabupaten OKU - Nourma Wulanda; Palupi Indah Sari; Mailani Rabiulkhri; M. Apriliansyah R.; Arif Aminullah (Kesejahteraan Bersama : Jurnal Pengabdian dan Keberlanjutan Masyarakat, 2026)
Fish smoked processing (salai ikan) is a driving sector of the local economy in Batumarta II Village, Lubuk Raja District, Ogan Komering Ulu (OKU). However, local MSMEs still face structural barriers, including limited conventional marketing scope and unrecorded financial management. This community service aims to accelerate digital transformation for smoked fish MSMEs to expand their market reach and professionalize business operations. The method used in this program follows the asset-based community development (ABCD) approach, which involves four main stages: laying the foundation, planning, information gathering, and acting on findings. The execution of the program included branding reconstruction through vacuum packaging, training on managing digital marketplaces and social media platforms, and digital bookkeeping via mobile applications. The results of this intervention showed significant behavioral shifts among the local business owners, including the establishment of active e-commerce channels and structured capital segregation. Digitization efficiently eliminates predatory intermediaries, allowing fish processors to secure up to a 35% increase in profit margins.